Navigating Digital Transformation: Examining the Role of Employee Integration in Shaping Intention to Stay - Lama, Annete; Lestari, Sri; Septiana, Puspa Avinda Dwi; Prasetyaningtyas, Sekar (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study investigates the role of organizational culture, organizational commitment, employee integration, and technology adoption in shaping employees’ intention to stay within the Indonesian construction sector, with a focus on PT PP (Persero) Tbk. In the era of digital transformation and artificial intelligence (AI) integration, retaining skilled employees has become a strategic priority to sustain competitiveness and operational stability. A quantitative method was employed, gathering data from 326 employees through an online survey, which were then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that organizational culture strongly promotes organizational commitment, which subsequently enhances employees’ intention to remain, thereby confirming the mediating effect of commitment. Employee integration likewise exerts a positive influence on retention intention. Nonetheless, organizational culture by itself does not directly impact intention to stay, and the hypothesized moderating effect of technology and AI adoption on the link between integration and retention intention is not validated. These results underscore the importance of strengthening organizational commitment and employee integration strategies, while highlighting that technology adoption alone may not guarantee improved retention. The study contributes to the human resource management literature by emphasizing the nuanced interplay of cultural, psychological, and technological factors in employee retention, offering practical insights for organizations undergoing digital transformation.